Islam and Indonesian Culture (Rituals and Institutions) - Darwis, Muhajir; Mulyati, Sri; Rizki, M; Rusdahlia, Rusdahlia; Azan, Fadilah; Hidayah, Nurul; Agustina, Ica Tamara (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This article explores the relationship between Islam and culture in Indonesia, focusing on aspects of ritual and religious institutions. Indonesia itself has quite a bit of cultural diversity and religious traditions, so this journal aims to investigate various aspects of Islam in life in Indonesia and how this influences rituals and institutions in Indonesia. The first part discussed in this journal is tracing the development of Islam in Indonesia, how Islam is integrated with local culture, and how the Islamic movement in Indonesia influenced the formation of religious rituals and institutions. Then the journal will explore various types of Islamic religious rituals in Indonesia, as well as explore Islamic institutions in forming Islamic identity in Indonesia, as well as explore their relationship with local culture. By presenting an understanding of the relationship between Islam and culture in Indonesia, it is hoped that the journal can contribute to religious, social and cultural studies in Indonesia in the future. The research method used is a qualitative approach with a focus on literature analysis. The research will explore information from relevant journals, books and previous research to gain an in-depth understanding of the role of rituals and religious institutions in the lives of Indonesian society.